A Novel Monoallelic Nonsense Mutation in the NFKB2 Gene Does Not Cause a Clinical Manifestation - Kotlinowski, Jerzy; Bukowska-Strakova, Karolina; Koppolu, Agnieszka; Kosińska, Joanna; Pydyn, Natalia; Stawinski, Piotr; Wilamowski, Mateusz; Nowak, Witold; Józkowicz, Alicja; Baran, Jarosław; Płoski, Rafał; Jura, Jolanta (Frontiers in Genetics, 2019)
NF-κB signaling, acting through NFKB1 dependent canonical and NFKB2 dependent noncanonical pathways, plays a critical role in inflammatory and immune responses. Recent studies have associated mutations in these two genes with a common variable immunodeficiency (CVID). While evaluating a female patient seeking a diagnosis explaining her recurrent infections, we found a novel heterozygous c.1831C>T (p.Arg611*) nonsense mutation in the NFKB2 gene which introduces a Stop codon in the ankyrin repeat domain of p100. Whole exome sequencing analysis, followed by Sanger sequencing, identified this previously unknown mutation in two other family members. Penetrance of the c.1831C>T variant was assessed by flow-cytometry and protein expression in peripheral blood mononuclear cells (PBMC); whereas, activation of the NF-κB2 signaling pathway was examined through immunoblotting and real-time PCR. Heterozygous c.1831C>T variant led to the expansion of lymphocyte B subpopulations with concomitant reduction of plasmablasts, low IgG levels, and accumulation of p52 in PBMC. On the other hand, tested subjects had normal levels of IgM, IgA, IgE and no impairment in lymphocytes proliferation. Although evaluated patients did not fulfill all clinical features of CVID, their health should be monitored in the future for possible late manifestation of the disease. In conclusion, we showed that NFKB2 haplodeficiency caused by c.1831C>T nonsense mutation is asymptomatic, possibly due to the compensatory mechanisms and allele redundancy.